Islamic Leftist and Ecological Resistance in the Nahdliyyin Front for Resource Sovereignty - Yanuar Ramadhan, Iqbal; Ganjar Herdiansyah, Ari; Al Banjari, Husin; Hidayat , Mupid (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to understand the emergence of leftist Islamic thought as articulated by the FNKSDA (Nahdliyyin Front for Natural Resource Sovereignty). The primary focus is to examine the material and historical conditions that enabled the development of this thought. This research employs a qualitative document analysis as its method. In doing so, the researcher drew data from official FNKSDA documents, articles authored by FNKSDA activists, and relevant academic journals accessible to the researcher. I interpreted the collected data using a thematic approach guided by the Historic Materialism framework formulated by Michael Lowy. Based on the analysis results, the study finds that the material and historical conditions confronted by FNKSDA have significantly shaped its formulation of leftist Islamic thought. The formation of FNKSDA's thought is shaped by three particular conditions: the political-economic landscape of post-Reformasi Indonesia, the internal dynamics of the Nahdlatul Ulama organization, and the broader development of Islamic thought in Indonesia in the post-Reformasi era. The researcher contends that this study offers a valuable contribution to the broader scholarship on Islamic political thought in Indonesia.